Clostridium Butyricum 337279 shapes the gut microbiota to attenuate metabolic disorder in diet-induced obese mice - Zhang, Xuejiao; Li, Zhiyu; Cao, Junjun; Sun, Haipeng; Niu, Wenyan (Frontiers in Microbiology, 2025)
AimsObesity is one of the important challenges to public health worldwide. Dysbiotic intestinal microbiota is a key factor in the onset and progression of obesity and related diseases. Short chain fatty acids (SCFAs) derived from butyricogenic bacteria has beneficial effects on obesity. Clostridium Butyricum 337279 (C.B), one of the SCFA producing bacteria, has been used to treat inflammatory bowel disease. The effect of C.B on obese mice remains unclear.MethodsA high fat diet (HFD)-induced mouse model of obesity was constructed, and the mice were treated with C.B to examine their role on obesity and related metabolic disorder. RT-qPCR, Western blotting, immunohistochemical staining, and 16S rRNA gene sequencing were performed to investigate the role and mechanism of C.B. Plasma levels of BCAA and BCKA were detected by Shimadzu LC-20 AD liquid chromatography (LC) system.ResultsHere we demonstrated that oral administration of C.B effectively alleviated HFD-induced obesity and associated metabolic disorders, including glucose intolerance and hyperlipidemia, as well as systemic inflammation, as evidenced by reduced levels of LPS, TNF-α, and IL-1β. C.B alleviated intestinal flora imbalance and modulated the composition of gut microbiota and their metabolites in HFD-induced obese mice. It also significantly ameliorated intestinal barrier disorders by increasing protein level of tight junction proteins ZO-1 and occludin. Importantly, dietary C.B potentially suppressed bacterial biosynthesis of branched-chain amino acids (BCAA) and reduced the excessive accumulation of BCAA in plasma, suggesting its role in restoring BCAA metabolism of mice.ConclusionC.B intervention significantly ameliorated gut microbiota imbalance in obese mice and alleviated obesity-related metabolic disorders by upregulating the expression of tight junction proteins (ZO-1 and occludin), attenuating endotoxemia and systemic inflammation and reducing microbial-derived BCAA production.